Eutrombicula cochinocaensis infestation in llamas (Lama glama) in the Puna region of Argentina - Medina, Diego Martín Nicolás; Acuña, Francisco Antonio; Abalos, Marcos; Aguirre Castro, Laura Sabrina; Avellaneda Cáceres, Agustín; Zamar, María Inés; Micheloud, Juan Francisco (Springer, 2025)
This paper aims to describe a case of trombiculosis in llamas from the Puna region of Argentina caused by Eutrombicula cochinocaensis. Trombiculosis is a parasitic infestation caused by the larval form of trombiculid mites, commonly known as chigger mites. Six adult llamas out of eighteen (33%) were infested and showed dermatitis, hyperemia, and crusts together with an orange-dotted pattern. The chigger mites were found mainly in the hind limbs and the abdomen. Microscopic identification of E. cochinocaensis was made by phase-contrast microscopy. Then, a histopathological study of the affected animals’ skin was performed. Histological findings included dermatitis withmainly lymphocytic infiltrate, pustules, crusts, hyperkeratosis, and the mites’ stylostomes in the dermis and epidermis. This is the first report of trombiculosis caused by E. cochinocaensis in llamas from Argentina. Mites of the family Trombiculidae are vectors of certain diseases to humans and animals and are therefore of sanitary and productive importance.